Chemical Constituents from the Fruits of Cotoneaster microphylla Wall ex Lindl - Bisht, G. (Asian Journal of Chemistry, 2010)
The fruits of Cotoneaster microphylla have been studied for its chemical analysis and found to consist of betulinic acid, ursolic acid and 1 : 4 : 3 : 6-dianhydro-D-mannitol.